The Motivation of Man to Work: Impact of the Global Economic Crisis Study - Nars, Felipe Carvalho F.; Ferreira, Marcos Aurelio de A.; Fischer, André Luiz (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346595534 The general objective of this research is to identify significant differences in the levels of ‘Satisfactionand Motivation’ among employees of the Best Companies to Work For in Brazil, elected by Guia VocêS/A-Exame, between 2007 and 2009. The specific objectives seek to: (1) verify if the result of the category‘Satisfaction and Motivation’ in 2009 differs significantly from 2007 and 2008, (2) assess the variations inthe indices that composes the result of this category in 2009 and relate them to the theory of motivation,and (3) identify elements in the speech of employees that demonstrate the actions taken by companiesbefore the global economic crisis in 2009 to keep them motivated and relate them to the theory of managementin the era of economic turbulence. The theoretical framework addresses three main issues: (1)organizational climate - its relationship to the organizational system and motivation, the importance ofits measurement through organizational climate surveys structured by categories and actions of seniormanagement due to its results. (2) Motivation - a conceptual overview and the recent discussion aboutthe meaning assigned to work as a source of motivation. (3) The management in the era of economicturbulence - the role of leadership dealing with new challenges of management in the chaos, clarity andeffectiveness communication due to maintain team morale in times of crisis. In order to find the answersto the proposed problem, we performed a descriptive analysis with focus on quantitative and qualitativedata. The survey sample was comprised of 66 companies that figured in the Guides for 2007, 2008 and2009. The Statistical analysis was given by applying the Kolmogorov-Smirnov (KS) test, additionally theGeneral Linear Model (GLM) and the selection method of Wilks Lambda. The quantitative results obtainedby applying hypothesis and comparison tests between means showed a drop in the levels of ‘Satisfactionand Motivation’ in 2009 compared to 2007 and 2008. From this result, we applied two methodsof qualitative analysis (exploratory data analysis and discourse analysis), in order to verify the possibleinfluence of global economic crisis on this result. Qualitative results show seven points of attention, fiveof which had higher negative change between 2008 and 2009 and only two showed positive growthbetween 2008 and 2009. In addition to these points of attention, the qualitative analysis according tothe speech of employees identified some actions taken by companies about leadership, communicationand maintenance of morale, corroborating the theory presented. The study’s findings point to the fallinglevels of ‘Satisfaction and Motivation’ in 2009 and the efforts of management focused on overcoming thecrisis. Some practical recommendations are submitted to the HR community, so that in times of economicturbulence they might be applied in order to mitigate potential negative impacts explained by research.